The Study of Ontology and Academic Ethics in Understanding the Nature of Education's Existence - Widialistuti, Refny; Fitri, Yuliani; Mulia, Vivi Sri; Safitri, Diah Amanda (The Future of Education Journal, 2026)
This study examines the integration of ontology and academic ethics in understanding the essence of education, with a focus on mathematics education. Using a qualitative conceptual approach through library research, this study analyzes scholarly works on educational ontology, academic ethics, and education. The findings show that education is ontologically an existential process aimed at the holistic formation of human beings, not merely knowledge transmission. In education, this perspective positions educations as an intellectual activity that shapes rational thinking and academic responsibility. The study also finds that academic ethics is an inherent consequence of understanding the nature of education and knowledge. Integrating ontological understanding and academic ethics is therefore essential for strengthening integrity and ethical practices in education, particularly in the digital era.